Optimal Sizing and Economic Analysis of Community Battery Systems Considering Sensitivity and Uncertainty Factors - Ragab, Ziad Hatem Anwar Aly (Curtin University, 2024)
This thesis presents a valuable contribution to the field of community battery systems by proposing a comprehensive model for optimizing their size and operation using PSO algorithm, taking into account the economic analysis side with consideration of uncertainty factors using the Monte Carlo simulations based on probabilistic distribution. The influence of different tariff structures is also assessed over 5 different structures. The outcomes offer valuable insights for policymakers and stakeholders in the energy sector to facilitate a more sustainable future.